Investigating the Star Formation Characteristics of Radio Active Galactic Nuclei - Bojun Zhang; Fan Zou; W. N. Brandt; Shifu Zhu; Nathan Cristello; Qingling Ni; Yongquan Xue; Zhibo Yu (The Astrophysical Journal)
The coevolution of supermassive black holes and their host galaxies represents a fundamental question in astrophysics. One approach to investigating this question involves comparing the star formation rates (SFRs) of active galactic nuclei (AGNs) with those of typical star-forming galaxies. At relatively low redshifts ( z ≲ 1), radio AGNs manifest diminished SFRs, indicating suppressed star formation, but their behavior at higher redshifts is unclear. To examine this, we leveraged galaxy and radio-AGN data from the well-characterized W-CDF-S, ELAIS-S1, and XMM-LSS fields. We established two mass-complete reference star-forming galaxy samples and two radio-AGN samples, consisting of 1763 and 6766 radio AGNs, the former being higher in purity and the latter more complete. We subsequently computed star-forming fractions ( f _SF ; the fraction of star-forming galaxies to all galaxies) for galaxies and radio-AGN host galaxies and conducted a robust comparison between them up to z ≈ 3. We found that the tendency for radio AGNs to reside in massive galaxies primarily accounts for their low f _SF , which also shows a strong negative dependence upon M _⋆ and a strong positive evolution with z . To investigate further the star formation characteristics of those star-forming radio AGNs, we constructed the star-forming main sequence (MS) and investigated the behavior of the position of AGNs relative to the MS at z ≈ 0–3. Our results reveal that radio AGNs display lower SFRs than star-forming galaxies in the low- z and high- M _⋆ regime and, conversely, exhibit comparable or higher SFRs than MS star-forming galaxies at higher redshifts or lower M _⋆ .